2006
DOI: 10.1021/ja054967k
|View full text |Cite
|
Sign up to set email alerts
|

Air-Initiated Radical Polymerization of Lithium Salts of ω-(Undecamethylcarba-closo-dodecaboran-1‘-yl)alk-1-enes, CH2CH(CH2)n-2C(BMe)11- Li+

Abstract: We report an easy access to the salts of the LiC(BMe)11- anion, which greatly simplifies the synthesis of compounds carrying the -C(BMe)11- substituent, including the title anions. The previously recognized and puzzling spontaneous oligomerization of the solid lithium salts CH2=CH(CH2)(n-2)C(BMe)11- Li+ upon storage under ambient conditions is now shown to proceed by a radical mechanism, with the "naked" Li+ cation acting as a catalyst. The degree of polymerization is higher in solution, especially when azoiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 35 publications
2
38
0
Order By: Relevance
“…However, for a ring-closure-type radical clock, we [19] were able to show that complexation of the double bond of the intermediate hex-1-en-6-yl radical [20] to a lithium cation decreases the calculated activation barrier for the ring-closing rearrangement significantly. This effect is supported indirectly by recent work of Michl and co-workers, [21,22] who showed that "naked" lithium cations have a catalyzing effect on the radical polymerization of terminal olefins, in accord with a proposal made 20 years ago on the basis of ab initio calculations [23] and a recent more-detailed study at higher theoretical levels. [24] However, all these observations pertain to radicals that contain a double bond, which can complex the lithium cation moderately well.…”
Section: Introductionsupporting
confidence: 59%
“…However, for a ring-closure-type radical clock, we [19] were able to show that complexation of the double bond of the intermediate hex-1-en-6-yl radical [20] to a lithium cation decreases the calculated activation barrier for the ring-closing rearrangement significantly. This effect is supported indirectly by recent work of Michl and co-workers, [21,22] who showed that "naked" lithium cations have a catalyzing effect on the radical polymerization of terminal olefins, in accord with a proposal made 20 years ago on the basis of ab initio calculations [23] and a recent more-detailed study at higher theoretical levels. [24] However, all these observations pertain to radicals that contain a double bond, which can complex the lithium cation moderately well.…”
Section: Introductionsupporting
confidence: 59%
“…48,164 Typical examples of introduction of substituents into the CB 11 H 12 -cage using electrophilic reagents are shown in Schemes 6 and 7. 15 The mechanism of these substitutions has not been studied in detail.…”
Section: Reactivity Patternsmentioning
confidence: 99%
“…The undecamethylated 1-iodo (222) and 1-bromo (221) anions are available 48 and have been converted with n-butyllithium or tert-butyllithium to the 1-lithio derivative of 12. 164 The lifetime of this extremely strong base in THF is limited to a few hours but is sufficient for ω-alkenylation with CH 2 dCH-(CH 2 ) n-2 -OTos (n ) 3-7) 164 and presumably for other electrophilic substitution reactions. Unfortunately, among the 1-halogenated (7-12)-hexamethylated anions only the chloro and fluoro derivatives are easily accessible, 48 and they do not undergo halogen-metal exchange, so this access to the deprotonated 11 currently remains blocked.…”
Section: Electrophilicmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionalized monocarba-closo-dodecaborate anions are used as building blocks in a variety of applications [1][2][3][4][5], for example in ionic liquids [6,7] catalysis [8][9][10][11][12][13][14][15], pharmaceuticals [16,17] and polymers [18,19]. A consequence of the constantly growing demand for functionalized monocarba-closo-dodecaborate anions is the increasing search for efficient procedures for the derivatization of the {closo-1-CB 11 } cage [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%